Ficus Genome Database: A Comprehensive Genomics and Transcriptomics Research Platform - Peng Sun; Lei Yang; Hui Yu; Lianfu Chen; Ying Bao (Horticulturae, 2024)
Ficus is a significant genus within the Moraceae family, primarily native to tropical and subtropical regions. It plays a crucial role in the study of co-evolution and genetics in the fig–fig wasp symbiosis. Advancements in sequencing technology have facilitated whole-genome sequencing of several Ficus species, accumulating vast amounts of genomic and transcriptomic data available in public databases. To streamline data integration, display, and analysis, we developed the Ficus Genome Database (FGD), a consolidated platform for the genomic data of five Ficus species, and self-assembled transcriptome data for 24 fig ostiolar bracts. The FGD is currently home to a diverse array of data, encompassing genome and gene sequences, annotations of genes, transcriptome analyses, biochemical pathways, non-coding RNA, and findings from comparative genomic studies, such as collinear blocks across different Ficus genome assemblies. To enhance translational and practical research concerning Ficus, FGD provides an extensive suite of accessible query interfaces, analytical instruments, and visualization options. These include the NCBI BLAST sequence search tool and the JBrowse/GBrowse genome browser. FGD also offers several distinct tools, including a genome Synteny Viewer, expression heatmap display, gene family identification, Gene Ontology terms enrichment, and pathway enrichment analysis.